Flexural Response of Slotted Ferrocement Beams to Third-Point Loading - C. ACMA, LEONCIO MARIANO; N. OREJUDOS, JERSON; S. MOSTRALES, DANIEL; G. TRINIDAD, ARISTON; B. NARIDO , JOSE PROSPERITO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper presents the results of the study on the flexural response of slotted ferrocement beams to third-point loading. A total of thirty-five specimens are tested considering five treatments with seven replications each. The set-ups covered in the study are as follows: use of one layer and two layers of wire mesh reinforcements, use of deformed bar and use of both deformed bar and one layer of wire mesh reinforcements. A set of specimen with no reinforcement is used as control. Flexural strength tests are carried using a Universal Testing Machine (UTM) at a loading rate of 5 kN/m. Cracks spacing and location are measured using a ruler while crack widths are measured using vernier and micrometer calipers. Deformed bar reinforcement has significant contribution to the flexural strength of the beam. The wire mesh reinforeement added to the deformed bar reinforcements significant ncreased the moment capacity and modulus of rupture. Frthermore, the provision of wire mesh decrease the spacing and width of cracks and increases the number of craks at failure leading to an increase of flexurial Strength.